Etiology, risk factors and sex differences in ischemic stroke in the Ludwigshafen stroke study, a population-based stroke registry - Palm, Frederick; Urbanek, Christian; Wolf, Johanna; Buggle, Florian; Kleemann, Thomas; Hennerici, Michael G.; Inselmann, Gerhard; Hagar, Mohammed; Safer, Anton; Becher, Heiko; Grau, Armin J. (Cerebrovascular diseases, 2012)
Background: Stroke etiology in ischemic stroke guides preventive measures and etiological stroke subgroups may show considerable differences between both sexes. In a population-based stroke registry we analyzed etiological subgroups of ischemic stroke and calculated sex-specific incidence and mortality rates. Methods: The Ludwigshafen Stroke Study is a prospective ongoing population-based stroke registry. Multiple overlapping methods of case ascertainment were used to identify all patients with incident stroke or transient ischemic attack. Modified TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria were applied for subgroup analysis in ischemic stroke. Results: Out of 626 patients with first-ever ischemic stroke in 2006 and 2007, women (n = 327) were older (73.5 ± 12.6 years) than men (n = 299; 69.7 ± 11.5 years; p < 0.001). The age-adjusted incidence rate of ischemic stroke was significantly higher in men (1.37; 95% CI 1.20-1.56) than in women (1.12; 95% CI 0.97-1.29; p = 0.04). Cardioembolism (n = 219; 35.0%), small-artery occlusion (n = 164; 26.2%), large-artery atherosclerosis (n = 98; 15.7%) and ‘probable atherothrombotic stroke’ (n = 84; 13.4%) were common subgroups of ischemic stroke. Stroke due to large-artery atherosclerosis (p = 0.025), current smoking (p = 0.008), history of smoking (p < 0.001), coronary artery disease (p = 0.0015) and peripheral artery disease (p = 0.024) was significantly more common in men than in women. Overall, 1-year survival was not different between both sexes; however, a significant age-sex interaction with higher mortality in elderly women (>85 years) was detected. Conclusions: Cardioembolism is the main source for ischemic stroke in our population. Etiology of ischemic stroke differs between sexes, with large-artery atherosclerotic stroke and associated diseases (coronary artery disease and peripheral artery disease) being more common in men.